2015
DOI: 10.1039/c5lc00045a
|View full text |Cite
|
Sign up to set email alerts
|

Mixing with herringbone-inspired microstructures: overcoming the diffusion limit in co-laminar microfluidic devices

Abstract: Enhancing mixing is of uttermost importance in many laminar microfluidic devices, aiming at overcoming the severe performance limitation of species transport by diffusion alone. Here we focus on the significant category of microscale co-laminar flows encountered in membraneless redox flow cells for power delivery. The grand challenge is to achieve simultaneously convective mixing within each individual reactant, to thin the reaction depletion boundary layers, while maintaining separation of the co-flowing reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 52 publications
3
52
0
Order By: Relevance
“…The second study in this work characterized the crossover losses and reactant recirculation possibilities of both single and dual pass architectures [109]. Similarly, a study by Marschewski et al provided a thorough analysis of microfluidic mixing demonstrating the utility of a raised neutral region in between turbulence promoting herringbone structures to preserve co-laminar flow [110].…”
Section: Table 1 Major Co-laminar Flow Cell Performance Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second study in this work characterized the crossover losses and reactant recirculation possibilities of both single and dual pass architectures [109]. Similarly, a study by Marschewski et al provided a thorough analysis of microfluidic mixing demonstrating the utility of a raised neutral region in between turbulence promoting herringbone structures to preserve co-laminar flow [110].…”
Section: Table 1 Major Co-laminar Flow Cell Performance Developmentsmentioning
confidence: 99%
“…In general, this single-layer device platform has spawned many derivative studies [48], [50], [55], [76], [77], [80]- [83], [85], [113], [119]- [123] due to its simplicity of construction and the possibility for direct visualization of the co-laminar interface quality and reactant conversion through the clear PDMS channel substrate. This unique feature has recently been utilized to visually track and quantify the effect of herringbone mixers on crossover of reactants via micro particle image velocimetry [110]. It has also been shown that parallel and series multiplexing of these cells within the same PDMS layer is possible but suffers from low overall device power density due to the added area required for separate manifolds [37], [105], [107].…”
Section: Research Perspectivesmentioning
confidence: 99%
“…The conventional passive methods of increasing the mixing velocity involve decreasing the thickness of the fluid layers by changing the microchannel size ( [1], [2]) and extending the contact area with adjacent liquids. To increase the mixing velocity in the microchannel, an excitation of circulations in the flow and a curvature of the flow lines can be used.…”
Section: Introductionmentioning
confidence: 99%
“…For microfluidic chambers, it is ideal to conduct this mixing on-chip in order to reduce blood volumes. However, in addition to the well-documented challenges of mixing in low Reynolds number flows, [23][24][25] mixing with whole blood is further hindered by the low diffusivity of suspended blood cells. In this report, we describe a method for continuous on-chip recalcification of sodium citrate anticoagulated whole blood, hereafter referred to as citrated blood, for microfluidic flow assays.…”
mentioning
confidence: 99%
“…Mixing in microfluidic devices poses several well-documented challenges 24,25,27 due to low Reynolds number flows and high P eclet numbers. For a solution or suspension to be well mixed, there must be no concentration gradients.…”
mentioning
confidence: 99%